The Impact of Digital Capabilities and Green Technology Implementation on Operational Performance and Business Sustainability in the Manufacturing Industry in Bandung Regency (Sustainable Development Insights, 2026)
The manufacturing industry is facing increasing pressure to enhance operational efficiency while maintaining environmental sustainability. The integration of digital technologies and environmentally friendly production systems has become a key strategy for improving organizational performance and long-term sustainability. This study aims to examine the impact of digital capacity and green technology implementation on operational performance and business sustainability in manufacturing companies in Bandung Regency. The research employs a quantitative approach using survey data collected from 110 respondents working in manufacturing firms. Data were gathered through structured questionnaires using a five-point Likert scale to measure respondents’ perceptions of digital capacity, green technology implementation, operational performance, and business sustainability. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the assistance of SmartPLS 3 software. The results indicate that digital capacity has a positive and significant effect on operational performance, suggesting that companies with stronger digital capabilities are able to improve production efficiency and operational effectiveness. In addition, green technology implementation also significantly influences operational performance by enhancing resource efficiency and reducing environmental impact. The findings further reveal that digital capacity and green technology implementation positively affect business sustainability. Moreover, operational performance plays an important role in strengthening business sustainability in manufacturing companies. These findings highlight the importance of integrating digital transformation and environmentally responsible technologies as strategic drivers for improving operational efficiency and achieving sustainable business development in the manufacturing sector.
Keywords: Digital Capacity; Green Technology; Operational Performance; Business Sustainability; Manufacturing Industry